The Tradition of “Basunat” (Genital Circumcision) in Female Children and Its Implication on Reproductive Health - Pratiwi Puji Lestari; Zaiyidah Fathony; Nia Fransiska Meylani; Ghaida Fitria Husna (Masters Program in Public Health, Sebelas Maret University, 2025)
Background: The tradition of basunat or circumsised on baby girls is still carried out by the Banjaresse in South Kalimantan as part of a cultural heritage that is believed to be related to purity, family honor, and a smooth delivery process. Although it has no medical basis and is prohibited by law, this practice is still preserved on the basis of social, cultural, and religious values that develop in the community. This study aims to examine the form of basunat implementation on baby girls in the Banjar community and evaluate its impact on reproductive health. Subjects and Method: This was a qualitative study with a descriptive-exploratory approach. The study was conducted in Tapin, Barito Kuala, Banjarmasin, and Banjar Districts of South Kalimantan, Indonesia. The informants were village shamans, midwives, indigenous people, and women who had been circumcised. Data were collected through documentation and in-depth interviews, then analyzed using data reduction techniques, narrative presentation, and drawing conclusions. Results: The study showed that the practice of circumcision is still commonly carried out symbolically and physically, generally by village shamans with traditional tools that are not sterile. The community still believes that circumcision can smooth the delivery process and is a cultural or religious obligation. However, this practice has the potential to have negative impacts on women's physical and psychological health Conclusion: Policy interventions that prioritize local culture-based education and the involvement of religious and community leaders are needed. This approach can help change public perception and support the sustainable elimination of this tradition.